Heterogeneous hematoma density predicts poor outcome in patients with supratentorial intracerebral hemorrhage after craniotomy - Li Luo; Yuanyuan Fu; Likun Wang; Jinhua Yang; Guofeng Wu; Siying Ren; Lian He; Shiqi Lin; Yuanyi Liu (BMC Neurology)
Abstract Background and Objective The density of hematoma is an imaging marker that has been used to predict hematoma expansion (HE) in patients with supratentorial intracerebral hemorrhage (SICH). However, its relationship with postoperative rebleeding and outcomes in surgical patients remains unclear. This study aimed to evaluate the impact of hematoma density on postoperative rebleeding and outcomes in patients with spontaneous supratentorial ICH after craniotomy. Methods This retrospective study included 331 patients with spontaneous SICH who underwent craniotomy at the affiliated Jinyang Hospital of Guizhou Medical University, between January 2019 and October 2023. Hematoma density was classified as heterogeneous if there were ≥ 3 low-density lesions within the ICH. The primary outcome measure was major disability, defined as a modified Rankin Scale score of 4–6. Patients were divided into homogeneous (n = 182) and heterogeneous (n = 149) groups based on computed tomography (CT) features at admission. A multivariate logistic regression model was used to analyze the independent correlation between hematoma density and postoperative rebleeding and poor outcomes. Results At 30 days and 6 months after craniotomy, among the 149 patients with heterogeneous density, 95 (63.8%) and 79 (53.0%) patients had a poor outcome, respectively. In contrast, among the 182 patients with homogeneous density, 74 (40.7%) and 61 (33.5%) had poor outcomes. Multivariate logistic regression analysis demonstrated that heterogeneous density independently predicts poor outcomes at 30 days (odds ratio 2.354; 95% confidence interval [1.446–3.833]; P<0.001) and 6 months (odds ratio 2.039; 95% confidence interval [1.268–3.279]; P=0.003) in patients with ICH after craniotomy but not rebleeding after craniotomy. Conclusions Heterogeneous hematoma density predicts poor outcomes at 30 days and 6 months in patients with spontaneous supratentorial ICH after craniotomy.